Effect of Basin Color on The Performance of Blue Swimming Crab (Portunus pelagicus) (Torani Journal of Fisheries and Marine Science, 2021)
Blue swimming crab (Portunus pelagicus) is a sea crab that is widely found in Indonesian waters. One of the determinants of the success of crab cultivation is the availability of quality seeds. Howewer, blue swimming crab hatchery is currently experiencing problems, namely unstable seed availiability due to high mortality and growth at the larvae stage. This research aims to evaluate the effect of various colors of rearing basins of feeding rate and survival rate of blue swimming crab larvae (P. pelagicus) in zoea stage. The larvae for the study was zoea-1 stage with a stocking density of 50 ind/L. The basins used in this study was a round plastic basin with a volume of 40 L filled with 30 L of media water. The feed used was rotifer and artemia nauplius. The method used was a completely randomized design consist of 4 treatments and 3 replications. The treatments that were the use black, green, blue, and red basins colors. The results of the analysis of variance showed that the color of the basins had a significant effect on the feeding rate (p < 0,05) and very significant on survival rate (p < 0,01) for small blue swimming crab larvae were produced in black basins 90.14 and 16.60%.